2021
DOI: 10.1108/jsm-07-2020-0282
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the experience value of mobile money transfer service: Senegaleseuser perspectives

Abstract: Purpose Digital service innovations have enabled service market access, transforming Africa. This paper aims to investigate individual and contextual drivers of experience value of mobile money transfer (MMT) service during post-adoption given impacts of individual/cultural characteristics in Senegal. Design/methodology/approach Mixed methods. Study 1 qualitatively investigates the effects of individual-contextual drivers on the experience value of MMT and behavioral intentions. Study 2 quantitatively tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Finally, our study treats technological characteristics as main stressors for resistance. However, prior studies have shown that individual difference such as traditional cultural orientation can influence mobile money transfer adoption (Fall et al , 2021). Future studies could explore how individual differences and design factors of mobile payment affect resistance to FRMPS.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study treats technological characteristics as main stressors for resistance. However, prior studies have shown that individual difference such as traditional cultural orientation can influence mobile money transfer adoption (Fall et al , 2021). Future studies could explore how individual differences and design factors of mobile payment affect resistance to FRMPS.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) reveal that as the share of deposits increases, the probability of using mobile banking service by microfinance institutions also increases. As per Fall et al. (2021), managers must focus on the following three aspects of experience value creation, viz.…”
Section: Resultsmentioning
confidence: 99%
“…The authors propose that even though the building blocks of the global B2B CX might be the same, they need to be adapted to the context. Moreover, Fall et al (2021) investigate individual and contextual drivers of the experience value of the mobile money transfer (MMT) service during the post-adoption phase, given the impact of individual and cultural characteristics. Through two studies conducted in Senegal, the authors found that the need for social interaction, self-efficacy and social pressure, must be considered and integrated into business practices.…”
Section: Different Ways Of Doing Businessmentioning
confidence: 99%